2018
DOI: 10.1111/1751-2980.12660
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of group D patients with negative serum anti‐Helicobacter pylori antibody and positive serum pepsinogen test in healthy Koreans

Abstract: A family history of GC and low baseline PGI/II were independently associated with an increased risk of progression of precursor lesions of GC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The emission of light was measured by the luminometer, which was related to the presence of anti- Hp IgG in the sample [ 17 ]. Values higher than 1.10 IU/mL were considered positive [ 18 ]. The Hp IgG kit has a sensitivity of 91% and a specificity of 100% [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…The emission of light was measured by the luminometer, which was related to the presence of anti- Hp IgG in the sample [ 17 ]. Values higher than 1.10 IU/mL were considered positive [ 18 ]. The Hp IgG kit has a sensitivity of 91% and a specificity of 100% [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…The HPG kit uses a chemiluminescent enzyme immunoassay, and has sensitivity and specificity of 91% and 100%, respectively [25]. Values higher than 1.10 IU/mL were considered positive [26]. To exclude false negative or positive results for anti- Hp IgG antibody, we reviewed serial changes of the titer in subjects who underwent multiple tests and referred to the results of rapid urease test or histologic examination of gastric tissue, if they were available.…”
Section: Methodsmentioning
confidence: 99%
“…In three of the five studies comparing atrophic versus non‐atrophic gastritis, 8,10–13 higher PgII levels were associated with non‐atrophic gastritis. In a large study by He and coworkers, 8 the status of the gastric mucosa was only assessed endoscopically 14 : patients with both non‐atrophic and atrophic gastritis showed significantly higher PgII serum levels than controls 15 . Taken together, the studies considered suggest that PgII is consistently associated with gastric inflammatory lesions (more than with atrophy).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the findings of the present review do not alter the skeptical conclusion reached by M. Tarek Al‐Assi in 1999, who wrote: “Despite a significant fall in serum markers of H . pylori infection in the groups of successfully treated individuals, no marker (PgII among others) tested in this study approached the reported accuracy of the urea breath test.” 15 …”
Section: Discussionmentioning
confidence: 99%